EESSI: A cross‐platform ready‐to‐use optimised scientific software stack. (16th February 2022) - Dröge, Bob; Holanda Rusu, Victor; Hoste, Kenneth; van Leeuwen, Caspar; O'Cais, Alan; Röblitz, Thomas
Abstract: Getting scientific software installed correctly and ensuring it performs well has been a ubiquitous problem for several decades now, which is compounded currently by the changing landscape of computational science with the (re‐)emergence of different microprocessor families, and the expansion to additional scientific domains like artificial intelligence and next‐generation sequencing. The European Environment for Scientific Software Installations (EESSI) project aims to provide a ready‐to‐use stack of scientific software installations that can be leveraged easily on a variety of platforms, ranging from personal workstations to cloud environments and supercomputer infrastructure, without making compromises with respect to performance. In this article, we provide a detailed overview of the project, highlight potential use cases, and demonstrate that the performance of the provided scientific software installations can be competitive with system‐specific installations.